The m6A RNA Demethylase ALKBH9B Plays a Critical Role for Vascular Movement of Alfalfa Mosaic Virus in Arabidopsis - Martínez-Pérez, Mireya; Gómez-Mena, Concepción; Alvarado-Marchena, Luis; Nadi, Riad; Micol, José Luis; Pallas, Vicente; Aparicio, Frederic (Frontiers in Microbiology, 2021)
The N6-methyladenosine (m6A) pathway has been widely described as a viral regulatory mechanism in animals. We previously reported that the capsid protein (CP) of Alfalfa mosaic virus (AMV) interacts with the m6A demethylase Arabidopsis protein ALKBH9B, regulating m6A abundance on viral RNAs (vRNAs) and systemic invasion of floral stems. Here, we analyze the involvement of other ALKBH9 proteins in AMV infection and we carry out a detailed evaluation of the infection restraint observed in alkbh9b mutant plants. Thus, via viral titer quantification experiments and in situ hybridization assays, we define the viral cycle steps that are altered by the absence of the m6A de-methylase ALKBH9B in Arabidopsis. We found that ALKBH9A and ALKBH9C do not regulate the AMV cycle, so ALKBH9B activity seems to be highly specific. We also define that not only systemic movement is affected by the absence of the demethylase, but also early stages of viral infection. Moreover, our findings suggest that viral upload into the phloem could be blocked in alkbh9b plants. Overall, our results point to ALKBH9B as a possible new component of phloem transport, at least for AMV, and as a potential target to obtain virus resistance crops.